Designing Employee Performance Monitoring Dashboard Using Key Performance Indicator (KPI) - Yance Gusnadi; Aditiya Hermawan (bit-Tech, 2019)
Institutions or companies must indirectly be ready to face the era of digitalization in presenting company information, especially to see employee performance. Many companies have not used an application that can help in the process of monitoring employees so far. The problem that occurs is that the company has been monitoring the process using a Spreadsheet which consists of inputting employee performance and reporting employee performance results with a predetermined target. In the process it takes a long time and tools to assist in monitoring and measuring employee performance. Dashboard monitoring is designed using the Key Performance Indicator (KPI) method that will help management and then focus on performance aspects that are used as a measure of company performance, which in turn the dashboard application with KPI will facilitate division heads and managers in conducting the analysis process, monitoring and evaluation. From the results of this research, the use of dashboard monitoring can facilitate the user in monitoring and measuring the KPI of each employee.